Investigation of Constraints that Occur during Participation in Leisure Activities by High School Students: A Sample of Turkey - Cihan Ayhan; Nurullah Emir Ekinci; İlimdar Yalçın; Şıhmehmet Yiğit (MDPI AG, 2018)
The aim of this research was to determine the factors that may prevent high school students from participating in recreational activities and to investigate whether these factors differ within the scope of various variables. This study consisted of 1459 (681 women and 778 men) student volunteers who are educated to high school level. The easy sampling method was preferred in the present study. The face-to-face survey method was used to collect the data. The “Leisure Constraints Scale” developed by Alexandris and Carroll (1997) and adapted to Turkish by Gürbüz, Öncü, and Emir (2012) was used to determine the factors that might prevent individuals from participating in leisure activities. The data obtained for the research were first transferred to a computer and then analyzed by the SPSS program. The error margin level in the study was taken as p < 0.05. The Cronbach alpha of the study was found to be 0.91. As a result, it was found that women participated in leisure activities more than men. It was also observed that the participants met with more leisure constraints in Turkey’s eastern regions.